Effects of adenosine on the growth of murine G:5:113 fibrosarcoma cells in vitro - Hofer, M; Hoferová, Z; Pospísil, M; Znojil, V; Chramostová, K (Folia biologica, 2003)
It has been observed that adenosine suppresses the growth of G:5:113 murine fibrosarcoma cells in vitro with EC50 of 178 mM. Changes in the cell cycle including decreased percentage of cells in S-phase, increased portion of cells in G0/G1-phase, as well as prolonged generation time were found to be responsible for the growth suppression. Dipyridamole, a drug inhibiting the cellular uptake of adenosine, enhanced the growth suppression induced with adenosine in concentrations of 100 and 200 microM. It follows from these results that the action of adenosine on the G:5:113 cells is extracellular, mediated by adenosine receptors. Elevation of extracellular adenosine might serve potentially as an anticancer therapeutic agent.
Keywords: Adenosine; fibrosarkom; buněčné dělení; Dipyridamole; Animals; dipyridamol; nádorové buněčné linie; Cell Division; buněčný cyklus; Cell Cycle; Fibrosarcoma; myši; adenosin; zvířata; Mice; Cell Line, Tumor